(untitled) (Fiep Bulletin - online, 2013)
We analyzed the scientific production about school Physical Education on the UFPE Teaching Postgraduation Program. Our sources were the CAPES Theses Data, the complete texts from the UFPE Digital Library of Theses, Essays and Dissertations and the printed material from the libraries of the public IES and the expert authors on the theme. The documental study and its summary was used to collect data and to analyze it, we employed the content analysis by its themes. At the moment, it is possible to identify an array of themes that include, in greater incidence, the critical-overcoming approach 9; the school curriculum 5; the educational policy 4 and sports 3; we also identified that 14 of the 28 dissertations and theses were concentrated under the orientation of one of the program teachers being equally distributed on the timeline; it was possible to realize that the qualitative research of critical and post-critical researches concentrated most of the studies